2008
DOI: 10.1016/j.ijpsycho.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilation in response preparation

Abstract: This study examined changes in pupil size during response preparation in a finger-cuing task. Based on the Grouping Model of finger preparation [Adam, J.J., Hommel, B. and Umiltà, C., 2003b. Preparing for perception and action (I): the role of grouping in the response-cuing paradigm. Cognitive Psychology. 46, (3), 302-358.; Adam, J.J., Hommel, B. and Umiltà, C., 2005. Preparing for perception and action (II) Automatic and effortfull Processes in Response cuing. Visual Cognition. 12, (8), 1444-1473.], it was hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…This would be in agreement with evidence that the pupillary response is affected by planning and executing a motor response (e.g., Hupé, Lamirel, & Lorenceau, 2009;Moresi et al, 2008). Indeed, Moresi et al found that the difficulty of response preparation during a finger-cuing task (Miller, 1982) was correlated with pupil size, with more-difficult cues eliciting larger pupil dilations during response preparation and execution.…”
supporting
confidence: 84%
“…This would be in agreement with evidence that the pupillary response is affected by planning and executing a motor response (e.g., Hupé, Lamirel, & Lorenceau, 2009;Moresi et al, 2008). Indeed, Moresi et al found that the difficulty of response preparation during a finger-cuing task (Miller, 1982) was correlated with pupil size, with more-difficult cues eliciting larger pupil dilations during response preparation and execution.…”
supporting
confidence: 84%
“…These studies show that the pupil size increases as the mental workload increases. Pupil dilation is also used to study other forms of cognitive effort, such as Stroop effects (Laeng, Ørbo, Holmlund, & Miozzo, 2011) the complexity of tasks (e.g., Moresi, Adam, Rijcken, van Gerven, Kuipers, & Jolles, 2008;Prehn, Heekeren, & van der Meer, 2011) and the difficulty of retrieving information from memory (van Rijn, Dalenberg, Borst, & Sprenger, 2012).…”
Section: Pupil Dilationmentioning
confidence: 99%
“…Bradley et al (2008) demonstrated that emotional arousal enlarged the pupil size, independent of the valence of the emotion. Moreover, in line with the putative arousing nature of cognitive control, an increased pupil dilatation has been shown to be a reliable measure of the extent of mental effort (Hess and Polt, 1964; Moresi et al, 2008), with a positive association between cognitive load and pupil dilatation (Steenhauer et al, 2000; see Kahneman, 1973). Indeed, pupil dilatation seems to reflect activity in the locus coeruleus-norepinephrine system (Jepma and Nieuwenhuis, 2011; Murphy et al, 2011), an arousal-related neurochemical system that is thought to play a key role in the cognitive control of behavior (Aston-Jones and Cohen, 2005).…”
Section: Introductionmentioning
confidence: 95%